Adaptation to the Risks of Digitalization: New Survival Trends for States in a Multipolar World - Julia V. Ragulina; Vladimir F. Ukolov; Oleg V. Shabunevich (Risks, 2021)
The purpose is to study the new survival trends for states in a multipolar world, determine the successfulness of adaptation to the digitalization of different growth poles, and develop the applied recommendations to improve the practice of adaptation to the risks of digitalization of these growth poles. Design/methodology/approach. The authors use the methods of economic statistics: variation analysis, trend analysis, correlation analysis, and regression analysis. Findings. The commonness of strategies of adaptation to the risks of digitalization for different poles of the world economy is substantiated, and two universal mechanisms—talent management and development of science—are found. The originality of this research is due to the consideration of digitalization from a new view—from the positions of setting states at the brink of survival due to the aggressive digital competition and high complexity of ensuring global competition in a quickly changing digital landscape. The uniqueness of this research is due to taking into account the specific features in a multipolar world. The practical implementation of the offered recommendations opens future perspectives for more successful survival trends in a multipolar world and the improvement of their adaptation to risks digitalization by 69.91% in G7 countries (on average) and by 88.40% in BRICS countries (on average).